2018
DOI: 10.1002/jrs.5458
|View full text |Cite
|
Sign up to set email alerts
|

On the criteria for the discrimination of inkjet printer inks using micro‐Raman spectroscopy

Abstract: Inkjet printers are ubiquitous devices in our society. Therefore, it is not surprising that they are used to commit different types of illicit activities such as threats or extortions by means of anonymous letters, frauds in the context of disputed contracts, alterations to or counterfeit of ID documents, or counterfeit of currency banknotes. This latter application is of primary interest in this study, where a method to rapidly develop investigative leads is required. Inkjet printed documents produce microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Buzzini and co‐workers discussed the criteria for the discrimination of inkjet printer inks using micro‐Raman spectroscopy. They concluded that although Raman spectroscopy is already a relatively well‐established method for the characterization of colourants (both dyes and pigments), this study demonstrates that the contribution of minor peaks within Raman spectra improves the discriminating capabilities of the technique . Jiao et al have provided solid confirmation for the origin of the low‐wave stray light in Raman spectra.…”
Section: Raman Techniques and Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Buzzini and co‐workers discussed the criteria for the discrimination of inkjet printer inks using micro‐Raman spectroscopy. They concluded that although Raman spectroscopy is already a relatively well‐established method for the characterization of colourants (both dyes and pigments), this study demonstrates that the contribution of minor peaks within Raman spectra improves the discriminating capabilities of the technique . Jiao et al have provided solid confirmation for the origin of the low‐wave stray light in Raman spectra.…”
Section: Raman Techniques and Methodsmentioning
confidence: 67%
“…They concluded that although Raman spectroscopy is already a relatively well-established method for the characterization of colourants (both dyes and pigments), this study demonstrates that the contribution of minor peaks within Raman spectra improves the discriminating capabilities of the technique. [205] Jiao et al have provided solid confirmation for the origin of the lowwave stray light in Raman spectra. They confirmed that the stray light mentioned above originates from the grating secondary maxima of Rayleigh scattering experimentally and theoretically.…”
Section: Instrumentation and Imagingmentioning
confidence: 97%
“…Buzzini P. and al [ 44 ]. discriminated coloured inkjet inks of different cartridge models using Raman spectroscopy.…”
Section: Inkjet and Toner Printingmentioning
confidence: 99%
“…Buzzini et al 127 analyzed inkjet printed samples by Raman using two laser excitations, 532 and 785 nm, to reveal Raman signals which had been undetected by one of the lasers due to resonance effects. PCA was used for more objective discrimination of the inks involved, although the authors claimed that no improvements were achieved from a visual comparison of the spectra.…”
Section: Raman Spectroscopy In Document Analysismentioning
confidence: 99%